Mechanisms of the effects of short-term inhalations of Xe and O2 gas mixture in the rehabilitation of post-covid ventilation failure - Udut, Vladimir V.; Naumov, Sergei Alexandrovich; Udut, Elena V.; Naumov, Sergei Sergeevich; Evtushenko, Diana Nikolaevna; Chumakova, O. N.; Zyuzkov, Gleb N. (Bulletin of experimental biology and medicine)
The article presents a theoretical rationale and a clinical case of relief of post-COVID ventilation failure by inhalation of Xe and O-2 gas mixture. Pneumonitis of coronavirus etiology transforms saturated phospholipids of surfactant into a solid-ordered phase, which disrupts surface tension, alveolar pneumatization, and alveolar-capillary gas exchange. Using molecular modeling (B3LYP/lanl2dz; GAUSSIAN09), we demonstrated that Xe atom due to the van der Waals dispersion interaction increases the distance between the phospholipid acyl chains providing a phase transition from the solid-ordered to liquid phase and restored the surface-active monolayer surfactant film. A clinical case confirmed that short-term inhalations of the Xe and O-2 gas mixture relieved manifestations of ventilation insufficiency and increased SpO(2) and pneumatization of the terminal parts of the lungs.